2007
DOI: 10.1158/1055-9965.epi-07-0306
|View full text |Cite
|
Sign up to set email alerts
|

Do Statins Affect Androgen Levels in Men? Results from the Boston Area Community Health Survey

Abstract: Background: In 2005, statins were among the most commonly used prescription medications in the United States. Some data suggest statins may affect cancer risk and/or disease severity. Because cholesterol is a required intermediate in sex steroid synthesis, it is possible that statins influence prostate cancer risk through effects on steroid hormone metabolism. We investigated whether levels of circulating androgens and their carrier protein, sex hormone -binding globulin (SHBG), varied by statin exposure among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 49 publications
(52 reference statements)
2
44
1
Order By: Relevance
“…Although the Finnish study did not observe an association between nonstatin cholesterollowering medications and advanced prostate cancer (3), this observation does not rule out a role for prostatespecific intracellular reductions in cholesterol synthesis. A recent paper suggested that cholesterol lowering by statins does not influence circulating concentrations of testosterone (42), the precursor for which is cholesterol. This observation possibly rules out one mechanism by which statins might influence advanced prostate cancer.…”
Section: )mentioning
confidence: 99%
“…Although the Finnish study did not observe an association between nonstatin cholesterollowering medications and advanced prostate cancer (3), this observation does not rule out a role for prostatespecific intracellular reductions in cholesterol synthesis. A recent paper suggested that cholesterol lowering by statins does not influence circulating concentrations of testosterone (42), the precursor for which is cholesterol. This observation possibly rules out one mechanism by which statins might influence advanced prostate cancer.…”
Section: )mentioning
confidence: 99%
“…There were no statistically significant interactions between NSAID use and arthritis history, and hormone levels tended to be lower among prescription NSAID users without a history of arthritis but not those with a history of arthritis, when compared to men with no NSAID use (data not shown). However, most differences in hormone levels for NSAID users vs. non-users were not statistically significant in either group; the exceptions were estrone, which was 22.5% lower among prescription NSAID users without arthritis (P=0.01), DHEAS, which was 26.6% lower among prescription NSAID users with a history of arthritis (P=0.02), and FSH, which was 18 There was no clear evidence of an association with type of over-the-counter NSAID use (aspirin vs. ibuprofen) or acetaminophen use (data not shown). Men who reported using aspirin but not ibuprofen had borderline significant lower levels of free estradiol (−11.4%, P=0.07) and LH (−8.5%, P=0.05) and significantly lower levels of FSH (−12.3%, P=0.01), compared to men with no prescription or over-the-counter NSAID use.…”
Section: Resultsmentioning
confidence: 80%
“…[16][17][18] Briefly, testosterone, SHBG, and DHEAS were measured by competitive electrochemiluminescence immunoassay, and LH and FSH were measured by sandwich electrochemiluminescence immunoassay, on the 2010 Elecsys system (Roche Diagnostics). DHT was measured by radioimmunometric assay (Diagnostic Systems Laboratories) and estradiol and estrone were measured by liquid chromatography-tandem mass spectrometry assay (ThermoFisher Scientific and Applied Biosystems-MDS Sciex).…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…The effects of treatment with statins on sex hormone levels have been addressed in multiple publications, but the results of these studies are equivocal [2][3][4][5][8][9][10][11][12].…”
Section: Statins and Total Testosterone Levelsmentioning
confidence: 99%
“…So it is reasonable to hypothesise that the use of statins may suppress steroidogenesis [2][3][4][5][6]. A certain role may also be played by other mechanisms of action identified in the case of statins, such as the inhibition of 17-hydroxysteroid dehydrogenase activity (simvastatin) [1,7].…”
Section: Introductionmentioning
confidence: 99%